Storage of Handroanthus umbellatus SEEDS - Martins, Cibele Chalita [UNESP]; Pinto, Monalisa Alves Diniz da Silva Camargo (My University, 2014)
Seed storage under controlled environmental conditions represents one of the most important lines of research to be applied on short-lived forest species as Handroanthus. The present research aimed to identify the most suitable seed storage conditions and longevity behavior of Handroanthus umbellatus seeds subject to the following storage treatments: packaging permeable paper bags under a no-controlled laboratory temperature and humidity (control) and multiwall semipermeable bag at temperatures of -18 ºC, 1 ºC and 25 ºC. Seeds were dried to 6.3% of water content. Stored seeds were evaluated every three months until 24 months for water content, germination percentage and vigor utilizing first counting test. Seeds of T. umbellata are orthodox, with low longevity under natural conditions, once they remain viable for less than 5 months. The best conditions of seed preservation of these species were obtained by storage at -18° C in multiwall bags. Under these conditions physiological seed quality remains unchanged for a 24-month period.
Armazenamento de sementes de ipê-amarelo-do-brejo (Handroanthus umbellatus (sond.) mattos. bignoniaceae)
Keywords: Handroanthus eximius; Seed preservation; Tabebuia umbellata; Vigor